Development of RP-HPLC method for simultaneous determination of docetaxel and curcumin in rat plasma: Validation and stability - Dong Wuk Kim; Abid Mehmood Yousaf; Dong Xun Li; Jong Oh Kim; Chul Soon Yong; Kwan Hyung Cho; Han-Gon Choi (Elsevier, 2017)
The purpose of the present research was to develop a suitable, simple, precise, accurate, robust, and reproducible RP-HPLC method for a reliable simultaneous quantification of docetaxel (DTX) and curcumin (CCM) in rat plasma samples using paclitaxel (PTX) as an internal standard. The samples were assayed by the Agilent 1260 Infinity HPLC instrument using a Capcell Pak C8 column (4.6 mm × 150 mm, 5 µm) under isocratic conditions. The mobile phase consisted of acetonitrile and triple distilled water (40/60, v/v) with a flow rate of 1.0 ml/min. The eluent was monitored at 230 nm for simultaneous measurement of curcumin and docetaxel. The method was validated by determining system suitability, selectivity, sensitivity, linearity, inter-day and intra-day precision, accuracy, robustness, and stability in accordance with the guidelines of the United States Food and Drug Administration (FDA). The developed chromatographic method proved to be simple, precise, accurate, robust and reproducible. Moreover, the samples showed stability at room temperature over a period of 48 h. Thus, this method would be employed for routine simultaneous quantification of docetaxel and curcumin in rat plasma samples.